Optimasi Desain Tubuh Bendung Boreng di Sungai Asem Kabupaten Lumajang - Lutfianto Cahya Rachmadan; Yudhi Lastiasih (Jurnal Impresi Indonesia, 2025)
The background of this research is the severe damage to the Boreng Dam in Lumajang Regency due to natural disasters, which disrupted irrigation and flood control functions. Significant differences between the 2017 and 2024 designs, both in terms of cost and structure, necessitate further analysis to determine the optimal design. The objective of this study is to compare the two designs in terms of stability, seepage, and cost efficiency, and to perform optimization to obtain the best solution. The research method starts from analyzing the difference between the 2017 design results and the 2024 design, then a calculation will be made on the bearing capacity of the pillar foundation. Using the Plaxis application, finite element method modeling was carried out on the stability of the weir body and examination of seepage. From the results of the study, the large price difference from the 2017 and 2024 designs is due to the difference in the type of weir markers that affect the volume of concrete, the use of K-300 concrete for the 2017 design is only found in the landmark blanket to the olak pond only, while the 2024 design also uses it on the upstream floor structure, then for the 2017 design does not use concrete pile foundations as many as 245 points like the 2024 design. The stability of the weir in the 2017 and 2014 designs both show a good level of safety with a safety factor value above 1.5 so that there is no need for additional reinforcement, but in the 2017 design it does not meet the lane seepage requirement with a minimum value of 8.5 for bare sandy soil, so optimization of the 2024 design is carried out with 2 modified models, namely reducing the depth of the pile from the original 6 meters to 3 meters and changing the dimensions to the original size of 40 x 40 cm to 25 x 25 cm. Material cost analysis for modification 1 showed a cost efficiency over the initial design of Rp. 259,554,225.00, while for modification 2 there was an efficiency of Rp. 884,561,475.00. The implication of this study is a recommendation to implement the 2024 design modification with 3-meter piles and dimensions of 25 x 25 cm as a safe and economical optimal solution.